Mental Flexibility Influences the Association Between Poor Balance and Falls in Older People – A Secondary Analysis - Pieruccini-Faria, Frederico; Lord, Stephen R.; Toson, Barbara; Kemmler, Wolfgang; Schoene, Daniel (Frontiers in Aging Neuroscience, 2019)
Impairments of balance predispose older people to falls. Some cognitive functions, especially executive functioning have been shown to affect balance and discriminate fallers from non-fallers. Mental flexibility is a component of the executive function and comprises multiple cognitive processes that work together to adjust the course of thoughts or actions according to the changing demands of a situation without the use of explicit instructions. However, the role of mental flexibility in balance in older people remains unclear. Mental flexibility comprises complementary cognitive functions required for dealing with unpredictable environmental demands. The study aim was to examine the relationship between mental flexibility and falls in a cohort of 212 older people (80.6 ±4.9 years; 62% female). We hypothesized that: (i) participants with impaired balance would have worse mental flexibility compared to those with good balance; and (ii) poor mental flexibility would predict falls in the sub-group with impaired balance. Balance performance was assessed by measuring postural sway while standing on a medium density foam mat with eyes open for 30 seconds. Mental flexibility was assessed using a computerized short-form of the Wisconsin Card Sorting Test (WCST; 64 cards) with its sub-components comprising general performance, perseveration, failure-to-maintain set and conceptual ability. Falls were measured prospectively for 12-months using monthly calendars. MANCOVA revealed that WCST performance was associated with balance (Wilks’ Lambda = 0.883, F=2.168; p=0.013, partial eta squared (η2p) =.061) due primarily to reduced concept formation ability (F2,207=5.787, p=0.004, η2p =.053). Negative binomial regression analysis adjusting for age, education, contrast sensitivity, proprioception, inhibition and inhibitory choice stepping reaction time revealed that lower concept formation ability was predictive for falls (Incidence Rate Ratio 1.0648 (95% confidence interval 1.0316-1.08199)). Further, lower concept formation ability partly explained the association between balance and falls: i.e. fallers in the upper balance tertile had reduced concept formation performance whereas non-fallers had similar concept formation performance across the three balance tertiles. These findings suggest that poor mental flexibility affects the ability to maintain steady balance contributing to increased risk of falls in older people.